(untitled) (Research, Society and Development, 2020)
The present article proposes to present a study about the importance and benefits of using of the Network Software Emulator Eve-NG (Emulator Virtual Environment), an application that has been highlighted by the possibility of emulating a network environment with from different manufacturers, without the need to install heavy applications on the client machine. Everything works in a web browser, and with the installation of an extension, it allows the text-mode terminal, the remote desktop sharing software, and Wireshark, a package capture software, inside the tool. You can work with equipment from the layers of Link, Network, Transport and even the Application Layer - the so-called final devices. In this work, a model was developed for the simulation of a network connecting three units of an organization in different states, through a MetroEthernet network with encrypted IPSec tunnels. Through this connection, Internet and corporate network access are provided using the BGP protocol for routing. Each state unit has a border firewall, which performs the conversion from private address to public, as well as have regional units also interconnected by a MetroEthernet network with IPSec and OSPF as routing protocol. The simulation allowed to analyze the behavior of the network, to make adaptations and corrections in the project, to create a training routine for the professionals of the area, to rationalize the implementation costs and to become a tool to support decision making by the Organization.